PERAN PENGELOLAAN SDM BERBASIS KOMPETENSI PEGAWAI ASN UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN PUBLIK PADA SEKRETARIAT DPRD KABUPATEN INDRAGIRI HILIR - Nurlian Susanti; Muhammad Fauzan; Dharmasetiawan Dharmasetiawan (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to determine the effect of competency-based human resource management of ASN (civil servants) on the effectiveness of public services at the Secretariat of the Regional House of Representatives (DPRD) of Indragiri Hilir Regency. This research uses a quantitative approach with a survey method. The population as well as the sample in this study consists of 60 ASN employees; therefore, the sampling technique used is saturated sampling. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression, t-test, and coefficient of determination (R²). The results of the study indicate that competency-based human resource management has a positive and significant effect on the effectiveness of public services. This is evidenced by the t-test results, where the calculated t-value is greater than the t-table value at a significance level of 0.05. The coefficient of determination (R²) value of 78% shows that the effectiveness of public services is strongly influenced by competency-based human resource management, while the remaining 22% is influenced by other factors outside this study. Therefore, the better the implementation of competency-based human resource management, the higher the effectiveness of public services at the Secretariat of the DPRD of Indragiri Hilir Regency.